Impact Of Inflation Rate, Exchange Rate and Interest Rate On Foreign Direct Investment in Sri Lanka - Muraleetharan, P. (International educational scientific Research Journal, 2017)
Foreign Direct Investment have main role that affect the macroeconomics performance of any leading country. The objective of this research was to investigate whether uncertainty or fluctuations in Impact of Inflation rate, exchange rate and Interest rate on FDI in Srilanka. This Study was based on secondary and time series data. For this purpose 38 years data of Inflation Rat e, Exchange rate and Interest Rate on FDI for the period of 1978 to 2015 was collected from the Central Bank report of Srilanka. The tests of Correlation and regression analysis were applied through Eview software to check the relationship between Inflation rate, Exchange rate and Interest rate on FDI. The correlation results showed that there is positive significant relationship between Exchange rate and Foreign Direct Investment while in regression analysis the value of R-square = 0.679 which shows that the independent variable Exchange has 67% impact on dependent variable Foreign Direct Investment and research model is accurate. Policy incentives and macroeconomic variables have a high explanatory power. This means that the government should give more incentives to the investors so as to attract them. Sri Lankan government has to consider developing policies to improve the interest rate, exchange rate and rate of inflation. This will enhance the FDI inflows into Sri Lanka.
Keywords: Foreign direct investment; Inflation rate exchange rate; Interest rate